2018
DOI: 10.1177/1354068817740745
|View full text |Cite
|
Sign up to set email alerts
|

The missing left? Economic crisis and the programmatic response of social democratic parties in Europe

Abstract: How have social democratic parties responded to the recent economic crisis? For many observers, the Great Recession and the prevalence of austerity in response to it have contributed to a crisis of social democracy in Europe. This article examines the programmatic response of social democratic parties to this crisis in 11 Western European countries. It uses an original data set that records the salience that parties attribute to different issues and the positions that they adopt with regard to these issues dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(59 citation statements)
references
References 69 publications
3
53
0
1
Order By: Relevance
“…Tables for pre-crisis elections are not shown, as no statistically significant relationship between left/right party position and welfare preferences existed during this time. These findings are in line with the analysis of European social democratic party platforms, which shows a convergence between right-leaning parties in favour of neoliberal welfare reforms pre-crisis and a strong shift to the left in defence of the welfare state post-crisis (Bremer, 2018).…”
Section: Politicization Of Post-crisis Social Spendingsupporting
confidence: 89%
See 1 more Smart Citation
“…Tables for pre-crisis elections are not shown, as no statistically significant relationship between left/right party position and welfare preferences existed during this time. These findings are in line with the analysis of European social democratic party platforms, which shows a convergence between right-leaning parties in favour of neoliberal welfare reforms pre-crisis and a strong shift to the left in defence of the welfare state post-crisis (Bremer, 2018).…”
Section: Politicization Of Post-crisis Social Spendingsupporting
confidence: 89%
“…By contrast, right‐wing parties are likely to identify government regulations or the size of the state as problematic (Starke et al, ). Polarization over welfare should increase after the GFC, as left‐leaning parties renew support for the welfare state, in line with their traditional values, while conservative parties, informed by pro‐market ideology, are unlikely to shift their positions in favour of a more generous welfare state (Bremer, ). Informed by these theoretical expectations this article tests two main hypotheses:Hypothesis (H1): Crisis as critical juncture…”
Section: Theoretical Accountsmentioning
confidence: 99%
“…As the economy is an issue that challenger parties try to deemphasize (Rovny, ), mainstream parties sought to take advantage of political debate shifting onto economic matters by increasing their programmatic emphasis on material concerns. Research has already shown that social democratic parties sought to increase the salience of core left‐wing issues relating to welfare and economic liberalism following the onset of the Great Recession (Bremer, ). Some parties of the Right have also taken advantage of the crisis to introduce drastic cuts in social expenditure, as exemplified by the UK Conservative Party since 2010 (Taylor‐Gooby, ).…”
Section: Theoretical Expectationsmentioning
confidence: 99%
“…Our analysis focuses on the external shock produced by the Great Recession and on EU institutions’ response to the crisis: according to the literature, external shocks, such as an economic crisis, are some of the main drivers of change in party organization and programs (Bremer ; Harmel et al. ).…”
Section: The Rlps and The Sdps: Diverging European Visions?mentioning
confidence: 99%